Flow-induced oscillation patterns for two tandem cylinders with turbulence stimulation and variable stiffness and damping. (15th December 2020) - Yuan, Wenyong; Sun, Hai; Li, Hui; Bernitsas, Michael M.
Abstract: The oscillation patterns of two 1-DOF cylinder oscillators, undergoing VIV and galloping, are investigated in a free surface water channel for 3.2 × 10 4 ≤ Re  ≤ 1.2 × 10 5 . The cylinders are arranged in tandem and supported by springs for a range of different spring stiffness and damping parameters. The efficiency of a current energy converter (CEC), based on flow-induced oscillation (FIO) of multiple cylinders in tandem, is critically related to the cylinder oscillation patterns. Due to the limited number of studies on the FIO for multiple cylindrical or prismatic bodies, their oscillation patterns have neither been identified nor classified. The surfaces of the cylinders are modified by turbulence stimulation to enhance FIO. Three different center-to-center spacing, five stiffness, and six damping ratios, for a total of 90 sets of experiments were conducted. The current velocity range is from 0.34 m/s to 1.32 m/s. From more than 2000 tests, five major patterns, nine sub-patterns are identified and classified. The patterns are defined based on the amplitudes, frequencies and the phase angle differences between the two cylinders. The characteristics and mechanics of each oscillation pattern are explored and explained from the perspective of fluid-structure interaction (FSI). By systematically varying the parameters, the underlying hydrodynamic mechanisms, including the coupling level between vortices and cylinders, the shielding effect, the wake effect, and the stability states are revealed. Few preliminary observations on the connection between oscillation pattern and harnessed power by the tandem cylinders are reported. Highlights: Oscillation patterns identified for 2 tandem cylinders with turbulence stimulation. The characteristics and inducing mechanism of each pattern are explained. The effect of the downstream cylinder on the upstream cylinder FIO is identified. Multiple stages exist in galloping for a two-cylinder system due to nonlinearity.